An intraoral periapical radiographic study of nutrient canals as a diagnostic aid in systemic diseases and pathological conditions - Vanaja G Reddy; I M Ali; M C Shashikanth (Wolters Kluwer Medknow Publications, 2008)
Objectives: To correlate the prevalence of nutrient canals in healthy dentulous with healthy edentulous, diabetes mellitus, hypertension and periodontally compromised patients. Methods: Study was conducted on 500 subjects in the age group of 21-70 years. They were clinically and radiographically examined using intraoral periapical radiographs, and were statistically analyzed. Results: On Comparing with control group, prevalence of nutrient canals was observed to be highly significant in diabetes (27%, P< 0.001), significant in edentulous (22%, P< 0.01), hypertensive (21%, P< 0.01) and periodontitis (17%, P< 0.05) groups. Highly significant age wise prevalence was observed in edentulous and periodontitis groups and a significant increase in diabetes and hypertensive groups. Interpretation and Conclusion: Significant correlation was observed in diabetes, edentulous, hypertensive and periodontitis groups, when compared with healthy subjects. Increase in prevalence of nutrient canals on mandibular anterior IOPAR can be used as an adjunct diagnostic aid in systemic diseases like diabetes, hypertension and periodontitis.